2019
DOI: 10.3390/rs11020182
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Land Surface Temperature and Their Influencing Factors: A Case Study in Suzhou, China

Abstract: Land surface temperature (LST) is a fundamental Earth parameter, on both regional and global scales. We used seven Landsat images to derive LST at Suzhou City, in spring and summer 1996, 2004, and 2016, and examined the spatial factors that influence the LST patterns. Candidate spatial factors include (1) land coverage indices, such as the normalized difference built-up index (NDBI), the normalized difference vegetation index (NDVI), and the normalized difference water index (NDWI), (2) proximity factors such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 67 publications
(99 reference statements)
1
38
1
3
Order By: Relevance
“…e normalized difference water index (NDWI) and normalized difference bareness index (NDBaI) were analyzed for delineating the water content in vegetation and identifying the bareness of soil, respectively [33,34]. Feng et al [35] found a strong correlation between LST and NDBI followed by NDWI and NVDI in Suzhou city. Furthermore, the urban index (UI) was found to have a high correlation with surface temperature in Harare, Zimbabwe [36].…”
Section: Introductionmentioning
confidence: 99%
“…e normalized difference water index (NDWI) and normalized difference bareness index (NDBaI) were analyzed for delineating the water content in vegetation and identifying the bareness of soil, respectively [33,34]. Feng et al [35] found a strong correlation between LST and NDBI followed by NDWI and NVDI in Suzhou city. Furthermore, the urban index (UI) was found to have a high correlation with surface temperature in Harare, Zimbabwe [36].…”
Section: Introductionmentioning
confidence: 99%
“…This assumption can be violated by rapidly changing vegetation conditions or large changes in soil moisture, but neither of these conditions typically is relevant to an urban environment. [15][16][17] Air temperature variations tend to be much smaller in magnitude than corresponding LST variations. Therefore, our method computes and applies normalized MODIS LST spatial anomalies to disaggregate daily maximum NLDAS air temperature; the normalization procedure accounts for this difference in magnitude of variation.…”
Section: Nldas Meteorological Reanalysis 1 × 1 Km 2 Downscaled Tempermentioning
confidence: 97%
“…Identification of the dominant LST-related factors minimizing their adverse effects, was recognized as an important challenge by recent studies [35,98]. Extensive research demonstrated that LST is closely linked to many parameters: land-use patterns, land coverage, landscape structures and land-use configuration [99,100].…”
Section: The Role Of Urban Features On Thermal Patternmentioning
confidence: 99%